Strategi Branding Sirup Markisa Produk UMKM Yayasan Tunas Mulia Bantar Gebang Kota Bekasi Jawa Barat - winarni, winarni; Simanjuntak, Victor Andreas; Setyarini, Dewi (LUGAS Jurnal Komunikasi, 2022)
This study aims to find out the branding strategy of the Manager of the Alam Tunas Mulia Foundation which produces Passion Fruit Syrup. MSME products packaged in bottles are recognized as products without preservatives, the taste is sweet and sour because they are without additives.   Branding here is intended to include the activities of creating, developing, implementing, managing passion fruit syrup products continuously until the brand of the syrup product becomes strong (Brand Equity). The results showed that the manager of the Passion Fruit Syrup product   had implemented a branding strategy for their products. However, this activity has not been implemented optimally. It still needs a more organized strategy.   The branding strategy carried out is only trying to introduce the product to consumers and it is expected that consumers buy the product. Introduction of Passion Fruit Syrup products through the Instagram application, Personal Selling, Whatsapp, Blog, and Exhibition.   The management has not conducted a consumer evaluation of the product